The analysis of forward acceleration asymmetries during on-water sprint kayaking - Goreham, J. A.; Ladouceur, M. (ISBS Proceedings Archive (Michigan), 2022)
The study`s aims were to (1) determine normative values of the critical features of forward acceleration asymmetries in sprint kayaking, and (2) to investigate the effect of stroke rate (SR) on these asymmetries. Fifteen national-to-world class level sprint kayak athletes completed four, 30-second on-water trials at four different SR`s (60, 80, 100, and maximum strokes per minute). Critical features (i.e., maximum, minimum and range) from forward acceleration waveforms were extracted from ten single stroke cycles (i.e., five left and five right) for each trial. An asymmetry index (ASI) was used to determine the amount of asymmetry between left and right strokes for each critical feature. ASI`s of at least 8.0±11.7% up to 19.3±12.4% existed for all critical features combined. A one-way repeated measures ANOVA with linear trend analyses showed all critical feature ASI`s increased with SR. These results provide appropriate asymmetry benchmarks for coaches to assess technical efficiency during on-water sprint kayaking and exude the importance of analyzing left and right single strokes separately.